An Immune Panel Signature Predicts Prognosis of Lung Adenocarcinoma Patients and Correlates With Immune Microenvironment - Zhou, Yuan; Tang, Lu; Chen, Yuqiao; Zhang, Youyu; Zhuang, Wei (Frontiers in Cell and Developmental Biology, 2021)
Background: Lung cancer, especially lung adenocarcinoma (LUAD) with high incidence, seriously endangers human life. The immune microenvironment is one of the malignant foundations of LUAD, but its impact at the molecular level is incompletely understood. Method: A total of 34 LUAD samples form Xiangya Hospital were collected for immune oncology (IO) profiling. Univariate Cox analysis was performed to profile prognostic immune genes based on our immune panel sequencing data. LASSO algorithm was applied to construct a risk signature. The cut-off threshold of risk score was determined using X-tile software. Kaplan-Meier survival curves and receiver operating characteristic (ROC) curves were employed to examine the performance of this risk signature for predicting prognosis. The immune infiltration was estimated using single-sample gene set enrichment analysis (ssGSEA) algorithm. Result: Thirty-one immune genes were profiled to be significantly correlated with the progression free survival (PFS) in our cohort. Among them, BST2, KRT7, LAMP3, MPO, S100A8, and TRIM29, were selected to construct a risk signature. Patient with a higher risk score demonstrated a significantly shorter progression free survival (p = 0.007). Time-dependent ROC curves indicated that our risk signature had a robust performance in accurately predicting survival. Specifically, the 6-, 12-, and 18-month area under curve (AUC) was 0.800, 0.932, and 0.912, respectively. Furthermore, the risk signature was positively related to N stage, tumor stage, and tumor malignancy. These results were validated using two external cohorts. Finally, the risk signature was significantly and uniquely correlated with abundance of neutrophil. Conclusion: Our study revealed an immune-panel based signature that could predict the prognosis of LUAD patients and was associated with the infiltration of neutrophil.